2022
DOI: 10.1371/journal.pone.0262894
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of a randomized controlled trial comparing mifepristone and misoprostol with misoprostol alone in the treatment of early pregnancy loss

Abstract: Background In case of early pregnancy loss (EPL) women can either choose for expectant, medical or surgical management. One week of expectant management is known to lead to spontaneous abortion in approximately 50% of women. Medical treatment with misoprostol is known to be safe and less costly than surgical management, however less effective in reaching complete evacuation of the uterus. Recently, a number of trials showed that prompt treatment with the sequential combination of mifepristone with misoprostol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…A pesar de ser comparativamente menos efectivo que el manejo quirúrgico en la evacuación uterina completa, el misoprostol tiene un perfil de seguridad similar al de los métodos de aspiración endouterina (manual y eléctrica) y es mucho más seguro que el legrado. Además, es un fármaco económico y ampliamente disponible (57)(58)(59)(60).…”
Section: Resultado Secundariounclassified
“…A pesar de ser comparativamente menos efectivo que el manejo quirúrgico en la evacuación uterina completa, el misoprostol tiene un perfil de seguridad similar al de los métodos de aspiración endouterina (manual y eléctrica) y es mucho más seguro que el legrado. Además, es un fármaco económico y ampliamente disponible (57)(58)(59)(60).…”
Section: Resultado Secundariounclassified
“…analysis of outpatient-based intervention for treatment of early pregnancy loss reported that the health state (measured by Short Form Six Dimension) was reduced by 0.0367 over 2 weeks [6]. The present model adopted 0.0367 as the disutility value for the three outpatient-based interventions (USG-MVA with cervical preparation, expectant care and misoprostol).…”
Section: Plos Onementioning
confidence: 95%